Hepatoprotective effects of hexane root extract of Alchornea laxiflora in sodium arsenate toxicity in wistar albino rats - Esosa Samuel Uhunmwangho; Nurudeen Olajide Rasaq; Iyanuoluwa Olubukola Osikoya (Wolters Kluwer Medknow Publications, 2018)
Background: Medicinal plants are have been used in the treatment of myriad disease conditions, Alchornea laxiflora is one of such medicinal plant. Aim: To investigate the hepatoprotective effect of hexane root extract of Alchornea laxiflora against sodium arsenate induced liver damage in wistar male rats. Setting and Design: Extraction and administration of bioactive extract. Materials and Methods: Extraction of air-dried ground root of Alchornea laxiflora was done by extracting 500 g with 500 cm of 95% hexane for 72 hrs.The animals (120-150 g) were pre-treated with the extract at varying doses (0.1, 0.5, 1.0, 10, 50 and 100 mg/kg body weight) for seven days orally prior to the intra-peritoneal administration of the toxicant (sodium arsenate) at a dose of 2 mg/kg body weight at the eight day. Hepatoprotective activity of the extracts was evaluated by studying the Cytochrome b5content, Glutathione-S-transferase and 4- Nitroanisole-o-demethylase activities in the liver, Plasma levels of Alanine aminotransferase (AST), Alanine aminotransferase (ALT), Alkaline phosphatase (ALP) and the levels of Total protein, Albumin, Globulin and Glutathione of the various groups. Statistical Analysis: The data were analysed with Microsoft excels (for windows 2007) and Student t-test and ANOVA. Result and Conclusion: The results suggest that pre-treatment of rats with hexane root extract of Alchornea laxiflora for seven days reduced the elevated levels of liver enzymes, reduced the levels of induced liver metabolizing enzymes and the levels of Total protein, Albumin, Globulin and Glutathione that was increased by the toxicity of sodium arsenate in rats and as such possess hepatoprotective effect against sodium arsenate.